Artificial Intelligence Today - Salihova Venera Karimjanovna (Global Scientific Publishing, 2023)
This article describes the history of developments in the field of artificial intelligence, determines the course of development of the science of artificial intelligence, reviews the status of various research and development systems at the current time, lists the main areas of research work in the field of artificial intelligence, presents the possibilities of using AI in various fields of human activities.
Keywords: Artificial intelligence; technology; neural systems; machine learning